1999
DOI: 10.1177/002215549904701103
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Evidence for the NO cGMP Signaling Pathway In Respiratory Ciliated Epithelia of Rat

Abstract: SUMMARY Airway epithelia play a crucial role in protecting the lung from the external environment. Ciliated airway epithelial cells contribute to mucociliary transport systems via ciliary beating and electrolyte transport mechanisms to defend against respiratory tract infection. Both of these activities are regulated by nitric oxide (NO)-dependent mechanisms. To better understand the role of the NO-cGMP signal transduction cascade in these responses, we investigated the localization of endothelial nitric oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…Although PKG-1 staining was additionally present in bronchial smooth muscle and alveoli, there was no detectable difference in staining intensity between control and CH lung tissue. Zhan et al (47) have similarly localized PKG-1␣ to pulmonary vascular and bronchial smooth muscle. However, in contrast to our present findings, PKG-1␤ was also found to be expressed in ciliated airway epithelial cells (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PKG-1 staining was additionally present in bronchial smooth muscle and alveoli, there was no detectable difference in staining intensity between control and CH lung tissue. Zhan et al (47) have similarly localized PKG-1␣ to pulmonary vascular and bronchial smooth muscle. However, in contrast to our present findings, PKG-1␤ was also found to be expressed in ciliated airway epithelial cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…Zhan et al (47) have similarly localized PKG-1␣ to pulmonary vascular and bronchial smooth muscle. However, in contrast to our present findings, PKG-1␤ was also found to be expressed in ciliated airway epithelial cells (47). The reason for this discrepancy is not clear but may be due to differences in protocols or antibodies used.…”
Section: Discussionmentioning
confidence: 99%
“…PKG and its role in flagellar or ciliary beating have not been as widely studied as the other protein kinases; only PKG-Ib has been detected on rat airway epithelial cells (Zhan et al 1999). It has been reported that NO regulates CBF via activation of PKG (Li et al 2000) and that NO is essential for maintaining ciliary motility Zhan et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Hsp90 is necessary for eNOS translocation to the apical membrane in response to increased luminal flow. Given the importance of eNOS-derived NO in the regulation of THAL NaCl absorption (35,38) and the role of eNOS in various physiological processes in epithelial cells of the respiratory tract, brain, and testis (14,29,55,57,60), this mechanism is likely to play an essential role in the regulation of NO levels in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that luminal flow induces eNOS translocation and activation in the THAL via PI3-kinase and that Hsp90 is involved in eNOS translocation to the apical membrane. nitric oxide; renal tubules; trafficking; phosphatidylinositol; heat shock protein; endothelial nitric oxide synthase IN POLARIZED EPITHELIAL CELLS of the kidney, respiratory tract, and testis, nitric oxide (NO) produced by endothelial NO synthase (eNOS) regulates important cellular functions (14,27,29,34,55,57,60). Thus eNOS activity and NO production must be tightly regulated in these cells.…”
mentioning
confidence: 99%